Farmer participatory research in cassava soil management and varietal dissemination in Vietnam: Results of phase 1 and plans for phase 2 of the Nippon Foundation project - Nguyen, The Dang; Tran Ngoc Ngoan; Dinh, Ngoc Lan; Le, Sy Loi; Thai Phien (International Center for Tropical Agriculture, 2001)
Farmer participatory research (FPR) in Vietnam has been carried out since 1994 as part of the Nippon Foundation project. This is a collaborative project between Thai Nguyen University of Agriculture and Forestry (TNUAF), the National Institute for Soils and Fertilizers (NISF) and the Centro Internacional de Agricultura Tropical (CIAT). The objective of the project is to enhance the adoption of soil conservation practices and improved cultural techniques in cassava fields. Two villages in Pho Yen district, Thai Nguyen province, one in Thanh Ba district, Phu Tho province, and one in Luong Son district, Hoa Binh province, were selected as pilot sites for implementing the FPR methodology in phase 1 (1994-1998). By using RRA and PRA methods in conducting the participatory diagnosis some limiting factors in cassava production were identified. Demonstration plots with 16 treatments on different ways to improve soil fertility and methods to control soil erosion were also established at Thai Nguyen University.\ Based on the results of the RRA and discussion, farmers selected four technical options, i.e. the use of contour hedgerows to control soil erosion, intercropping, application of fertilizers and new varieties, to test in FPR trials on their own fields. Result of the FPR trials on farmers fields indicate that the combination of intercropping with peanut, planting of contour hedgerows of vetiver grass or Tephrosia candida, and the use of a well-balanced NPK application were considered as the most promising practices at both pilot sites; these practices not only increased farmers’ income but also reduced soil erosion by 20-40% in comparison with the check plot of monocropping and without hedgerows. The results of the FPR trials were evaluated each year by the farmers during the field days at time of harvest and were used to plan the trials for the next year. After four years of research, farmers have adopted the application of balanced NPK fertilizers and some are establishing contour hedgerows of Tephrosia candida or vetiver grass. However, the widespread adoption of new cassava varieties by the farmers was the best result of the first phase of the project. New cassava varieties, such as KM60, KM94, KM95-3, and KM98-7, are now planted extensively, not only by farmers that participated in the research program but also by other farmers. FPR is the best method to develop and transfer technologies with farmers. The number of farmers that wanted to participate increased from 1994 to 1998, indicating the effectiveness of the participatory research approach. The main objectives in the second phase are: - To develop new and innovative FPR methodologies by using various methods of participatory research at about 20 pilot sites in Vietnam, in order to overcome constraints identified at the farm level. -To disseminate new technologies that increase income and help to conserve soil productivity, identified by farmers, to at least 3000 other cassava farmers. -To build and strengthen the capacity of researchers, extensionists and cassava farmers in using participatory approaches for self-development.